Technical analysis for the phrases of women foil fences /final rounds in the Olympics - Abdullah, Alaa (Journal of Physical Education, 2010)
The Research Technical Analysis for the competitions can provide us a large data to build technical Strategy, This study aimed to Technical Analysis of successful phrases for women foil fences in the Olympic Games - Beijing / 2008, trying to count the largest technical information related to the attack and defense foil weapon.The research subjects were sixteen fences of the final rounds of the foil weapon competition (Individual - team) . As has been analyzed 131 successful phrases is the number of touches achieved in these competitions.This study counted a lot of information, which is for attack and defense the researcher concluded the reliance on simple attack and simple skills in the implementation of the attack, the researcher recommended building technical strategies on the basis of simplicity without the complexity during the competition.